Revolusi Digital dan Tantangan Kriminologis: Analisis terhadap Tren Kriminalitas dalam Era Digitalisasi - Butarbutar, Jonner Marulitua (Media Hukum Indonesia (MHI), 2025)
Purpose: This study aims to analyse the impact of the digital revolution on the emergence and transformation of criminal behaviours. It focuses on understanding how digitalization has influenced the nature, method, and scope of crimes, particularly in the context of cybercrime, digital fraud, data exploitation, and hacking. Research Methodology: The research adopts a qualitative approach, utilizing literature review and theoretical analysis. Various contemporary criminological theories are employed to interpret the changing patterns of criminality in the digital era. Results: The study reveals that the digital revolution has significantly altered criminal behaviour. New types of crimes have emerged, characterized by their transnational nature, anonymity, and reliance on technological tools. These developments challenge traditional law enforcement mechanisms and demand updated frameworks for crime prevention and investigation. Conclusion: The evolution of crime in the digital age necessitates urgent reforms in legal, regulatory, and security systems. Traditional approaches are no longer sufficient to address the complexities of digital crime. A multidisciplinary and adaptive response is crucial. Limitations: This study is limited by its reliance on secondary data and theoretical frameworks. Further empirical research is needed to validate the findings and explore region-specific crime patterns in more detail. Contribution: The study provides a conceptual foundation for policymakers and legal practitioners to develop technology-based, forward-looking criminal justice policies. It also contributes to the academic discourse on the intersection between digital transformation and criminology.